Priority areas in management of diabetes mellitus type 1 & 2 (following 47th EASD Annual Meeting) - Ivona Renata Yarek-Martynova; Lyubov' Leonidovna Bolotskaya (Сахарный диабет)
Individualization of treatment goals is a modern trend in diabetology. During 47th Annual Meeting of European Association for the Study of Diabetesthis very problem was addressed repeatedly. The Sanofi Satellite Symposium under the name A step towards individualizing care to achieve earlyand sustained glycemic control presented lectures of worlds leading experts, giving priority to the problem of early diagnosis and early interventionfor individuals with T2DM, as well as potential benefits of early insulinisation, significance of adequate self-monitoring and pharmacoeconomicaspects of diabetes care.